1997
DOI: 10.1182/blood.v89.3.902
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutations in the Fas Gene Resulting in Autoimmune Lymphoproliferative Syndrome: A Molecular and Immunological Analysis

Abstract: Programmed cell death (or apoptosis) is a physiological process essential to the normal development and homeostatic maintenance of the immune system. The Fas/Apo-1 receptor plays a crucial role in the regulation of apoptosis, as demonstrated by lymphoproliferation in MRL-lpr/lpr mice and by the recently described autoimmune lymphoproliferative syndrome (ALPS) in humans, both of which are due to mutations in the Fas gene. We describe a novel family with ALPS in which three affected siblings carry two distinct m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(62 citation statements)
references
References 43 publications
1
60
0
1
Order By: Relevance
“…Recently, rare human counterparts of Fas mutations, some manifesting systemic autoimmunity, have been identified. [30][31][32] In addition, expression of Fas and FasL in tissues has been shown to promote organ-specific autoimmunity, as recently shown in Hashimoto's thyroiditis 33 and in the NOD diabetes model. 34 Although many cell types can express Fas, FasL initially seemed to be expressed only on activated T cells.…”
mentioning
confidence: 89%
“…Recently, rare human counterparts of Fas mutations, some manifesting systemic autoimmunity, have been identified. [30][31][32] In addition, expression of Fas and FasL in tissues has been shown to promote organ-specific autoimmunity, as recently shown in Hashimoto's thyroiditis 33 and in the NOD diabetes model. 34 Although many cell types can express Fas, FasL initially seemed to be expressed only on activated T cells.…”
mentioning
confidence: 89%
“…Whereas all the heterozygous family members were asymptomatic, homozygous patients developed a severe form of ALPS. 29 Similarly, the identification of compound heterozygous FAS mutations in three siblings (all of whom were severely affected, in contrast to their asymptomatic heterozygous parents) 30 suggested that some FAS mutations are recessive and others are dominant.…”
Section: Guishing Between Dn T Cells In Alps-fas/faslg From Other Dn mentioning
confidence: 99%
“…The combination of germline and somatic events explained the previously described but rare examples of compound heterozygous or homozygous germline FAS mutations. 28,30 This phenomenon might be involved in more common autoimmune diseases. A major remaining obstacle is the identification of the lymphocyte subset in which the somatically mutated cells accumulate.…”
Section: Guishing Between Dn T Cells In Alps-fas/faslg From Other Dn mentioning
confidence: 99%
“…Additionally, one family has been described in which two siblings are compound heterozygote's with distinct missense mutations in each FAS allele. 136 Interestingly, despite mutations in both FAS genes these patients have a milder ALPS phenotype. Also, unlike other patients with homozygous FAS mutations these patients did not have a family history of ALPS despite both parents being heterozygous for FAS.…”
Section: Alps Geneticsmentioning
confidence: 99%